Trust, Happiness, and Pro-Social Behavior - Stefano Carattini; Matthias Roesti (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper combines several large-scale surveys with different identification strategies to shed new light on the determinants of cooperative behavior. We provide evidence indicating that the well-being maximizing level of trust is above the income maximizing level. Higher trust is also linked to more cooperative and pro-social behaviors, including the private provision of global public goods such as climate change mitigation. Consistent with "warm glow" theories of pro-social behavior, our results show that individuals may enjoy being more cooperative than what would lead them to maximize their income, which is reflected in higher levels of well-being.
Keywords: Q50; H41; I31; D64; 330; cooperation; generalized trust; pro-social behaviour; pro-environmental behavior; well-being